Intra-Prostatic Injection of Epinephrine during Transurethral Resection of Prostate Reduces Blood Loss and Need for Blood Transfusions - Agha Zohaib, Adnan Siddiq, Salman El Khalid, Shoaib Mithani, Waqar Hassan, Mohammad Saleem (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the role of Intraprostatic injection of epinephrine intra-operatively in patients undergoing TURP in decreasing blood loss and the need for subsequent blood transfusions. Design: A double-blind, randomized controlled trial. Place and duration of study: The Kidney Centre Postgraduate Training Institute, Karachi, from March till August 2020. Methodology: A total of 40 patients were chosen at random and divided into two groups of equal size. One group got an intra-prostatic injection of epinephrine, whereas the other received a standard saline injection. Both groups were evaluated in terms of prostate volume (ml), resected tissue (gms), surgical resection time (minutes), pre and post-operative Hemoglobin (HB), and Hematocrit (HCT) levels. Intra-operative blood loss was then quantified using the last two variables. Transfusion requirement in both groups was also recorded. Results: Mean +Age of patients in Group A and Group B was 66.30+9.24years and 65.65+7.43years, respectively, with no significant difference between both groups (p=0.808). Median and IQR Prostatic volume in Group A and Group B was 68.0, 15, and 64.0,21, suggesting no statistically significant difference between the two groups (p=0.372). Mean + S.D Loss of HB of patients in Group A and Group B was 1.15 + 0.42 and 1.87+1.04, respectively, with a significant difference between both groups (p=0.007). Mean + S.D of post-op HCT patients in Group A and Group B was 3.16+1.50 and 4.81+2.79, revealing a significant difference between the two groups (p=0.026). No patients in Group A needed blood transfusions, whereas six patients in Group B had blood transfusions, indicating a statistical distinction between the two groups (p=0.001). Conclusion: The use of intra-prostatic injection of epinephrine leads to reduced blood loss and subsequently reduced operative time, irrigation fluid usage, and blood transfusion during TURP. It also allows a greater amount of prostatic tissue to be resected. Keywords: Transurethral resection of Prostate, Epinephrine, Blood transfusion, Hemoglobin, Hematocrit.